2005
DOI: 10.1107/s1600536805036780
|View full text |Cite
|
Sign up to set email alerts
|

3-Chloro-4-hydroxy-4′-methylbenzophenone

Abstract: The title compound, C14H11ClO2, possesses normal geometrical parameters. The two benzene rings are twisted by 54.70 (4)°, perhaps as a result of steric repulsion between H atoms. The crystal packing is consolidated by an O—H⋯O hydrogen bond, π–π stacking and C—H⋯O and C—H⋯π inter­actions, resulting in a two‐dimensional network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
(5 reference statements)
1
3
0
Order By: Relevance
“…1). Bond lengths and angles in the two molecules are similar, display normal values (Allen et al, 1987) and are comparable to those observed in related structures (Kutzke et al, 2000;Harrison et al, 2005). Each of the two unique molecules is twisted about C6-C7 and C7 -C8 bonds with dihedral angle between the phenyl (C8-C13) and benzene (C1-C6) rings of 24.29 5 (Bernstein et al, 1995) (Table 1 and Fig.…”
Section: S1 Commentsupporting
confidence: 70%
See 1 more Smart Citation
“…1). Bond lengths and angles in the two molecules are similar, display normal values (Allen et al, 1987) and are comparable to those observed in related structures (Kutzke et al, 2000;Harrison et al, 2005). Each of the two unique molecules is twisted about C6-C7 and C7 -C8 bonds with dihedral angle between the phenyl (C8-C13) and benzene (C1-C6) rings of 24.29 5 (Bernstein et al, 1995) (Table 1 and Fig.…”
Section: S1 Commentsupporting
confidence: 70%
“…For related literature on values of bond lengths, see: Allen et al (1987). For related structures, see: Harrison et al (2005); Kutzke et al (2000); Patai & Rappoport (1988); Thomson (1997); Zhang et al (2000). = 77.869 (1) V = 1149.83 (5) Å 3 Z = 4 Mo K radiation = 0.55 mm À1 T = 100.0 (1) K 0.69 Â 0.14 Â 0.13 mm…”
Section: Related Literaturementioning
confidence: 99%
“…For related structures, see: Cox et al (1997Cox et al ( , 2008; Harrison et al (2005); Malathy Sony et al (2005); Prasanna & Guru Row (2000); Xing et al (2005). For background to benzophenone derivatives, see: Colpaert et al (2004); Deleu et al (1992); Duncan et al (2004); Evans et al (1987); Ottosen et al (2003); Revesz et al (2004); Sieroń et al (2004); Wiesner et al (2002).…”
Section: Related Literaturementioning
confidence: 99%
“…4-Aminobenzophenones have high antiinflammatory activity (Ottosen et al, 2003), a benzophenyl cyano derivative acts as a vasorelaxant (Duncan et al, 2004) and the piperidinyl derivative produces analgesia (Colpaert et al, 2004). The crystal structures of some related compounds, viz., N-(2-benzoyl-4-chlorophenyl)-2-chloroacetamide (Malathy Sony et al, 2005), 2-chloroacetamido-5chlorobenzophenone and 2-chloroacetamido-5-chloro-2′-fluorobenzophenone (Prasanna & Guru Row, 2000), 2-methylamino-5-chlorobenzophenone (Cox et al, 1997), 2-amino-2′-chloro-5-methylbenzophenone (Xing et al, 2005) and 3chloro-4-hydroxy-4′-methylbenzophenone (Harrison et al, 2005) The title compound, C 13 H 9 ClN 2 O 3 , crystallizes with one molecule in the asymmetric unit with Z = 4. An intramolecular hydrogen bond between the carbonyl oxygen (O3) and an amine hydrogen atom (H1B) from the 2-amino-5-nitrobenzoyl group keeps these two groups nearly in the same plane releative to each other (Fig.…”
Section: S1 Commentmentioning
confidence: 99%